NLRP3 lacking the leucine-rich repeat domain can be fully activated via the canonical inflammasome pathway - Hafner-Bratkovič, Iva (Nat Commun, 2018)
NLRP3 is a cytosolic sensor triggered by different pathogen- and self-derived signals that plays a central role in a variety of pathological conditions, including sterile inflammation. The leucine-rich repeat domain is present in several innate immune receptors, where it is frequently responsible for sensing danger signals and regulation of activation. Here we show by reconstitution of truncated and chimeric variants into Nlrp3(−/−) macrophages that the leucine-rich repeat domain is dispensable for activation and self-regulation of NLRP3 by several different triggers. The pyrin domain on the other hand is required to maintain NLRP3 in the inactive conformation. A fully responsive minimal NLRP3 truncation variant reconstitutes peritonitis in Nlrp3(−/−) mice. We demonstrate that in contrast to pathogen-activated NLRC4, the constitutively active NLRP3 molecule cannot engage wild-type NLRP3 molecules in a self-catalytic oligomerization. This lack of signal amplification is likely a protective mechanism to decrease sensitivity to endogenous triggers to impede autoinflammation.